2022
DOI: 10.3390/diagnostics12102281
|View full text |Cite
|
Sign up to set email alerts
|

Prone Positioning Decreases Inhomogeneity and Improves Dorsal Compliance in Invasively Ventilated Spontaneously Breathing COVID-19 Patients—A Study Using Electrical Impedance Tomography

Abstract: Background: We studied prone positioning effects on lung aeration in spontaneously breathing invasively ventilated patients with coronavirus disease 2019 (COVID-19). Methods: changes in lung aeration were studied prospectively by electrical impedance tomography (EIT) from before to after placing the patient prone, and back to supine. Mixed effect models with a random intercept and only fixed effects were used to evaluate changes in lung aeration. Results: fifteen spontaneously breathing invasively ventilated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Moreover, the variability of tidal impedance can be affected by body position and respiratory efforts. 60 To date, 7 prospective studies 22,59,[61][62][63][64][65] on 10À25 intubated subjects with COVID-19 have investigated lung aeration and ventilation during PP, assessed by EIT and/or CT (Table 2). Unlike APP for non-intubated subjects, intubated subjects in most studies were found to have significant increase of lung aeration in dorsal regions and decreased aeration in ventral regions, as shown in Table 2 and Figure 2.…”
Section: Physiological Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the variability of tidal impedance can be affected by body position and respiratory efforts. 60 To date, 7 prospective studies 22,59,[61][62][63][64][65] on 10À25 intubated subjects with COVID-19 have investigated lung aeration and ventilation during PP, assessed by EIT and/or CT (Table 2). Unlike APP for non-intubated subjects, intubated subjects in most studies were found to have significant increase of lung aeration in dorsal regions and decreased aeration in ventral regions, as shown in Table 2 and Figure 2.…”
Section: Physiological Responsesmentioning
confidence: 99%
“…Pierrakos et al 65 assessed the change in ventilation using EIT in 15 subjects with COVID-19 who underwent PP for a median of 19 h. Notably, this is the only study where subjects had spontaneous breathing activity. The authors reported a significant improvement of aeration in dorsal regions and a non-significant decrease in the incidence of pendelluft phenomenon from 46% to 35%.…”
Section: Physiological Responsesmentioning
confidence: 99%
See 1 more Smart Citation